Health Trajectories of Family Caregivers: Associations With Care Transitions and Adult Day Service Use. (June 2015) - Liu, Yin; Kim, Kyungmin; Zarit, Steven H.
Objective: The study examines family caregivers' health changes over 1 year on four health dimensions and explores the association of differential health trajectories with adult day service (ADS) use and caregiving transitions.Method: The participants were 153 primary caregivers of individuals with dementia (IWDs) who provided information on care situations and their own health at baseline, 6-month, and 12-month interviews.Results: Caregivers showed increasing functional limitations and decreasing bodily pain over time, whereas role limitation and general health perception remained stable. Furthermore, caregivers' trajectories of functional limitation were associated with their extent of ADS use at baseline and their relatives' placement.Discussion: Health is multidimensional; all dimensions of caregiver health do not change in a uniform manner. The findings underscore the importance of the association of caregiving transitions and caregiver health and the potential health benefits of ADS use for family caregivers.